Foot and ankle joint movements inside orthoses for children with spastic CP. Issue 4 (23rd December 2013) - Liu, Xue‐Cheng; Embrey, David; Tassone, Channing; Klingbeil, Frederick; Marquez‐Barrientos, Carlos; Brandsma, Brenna; Lyon, Roger; Schwab, Jeffrey; Tarima, Sergey; Thometz, John
ABSTRACT We compared the ankle joint and foot segment kinematics of pediatric cerebral palsy (CP) participants walking with and without orthoses. A six segment foot model (6SF) was used to track foot motion. Holes were cut in the study orthoses so that electromagnetic markers could be directly placed on the skin. The Hinged Ankle Foot Orthoses (HAFO) allowed a significant increase in ankle dorsiflexion as compared to the barefoot condition during gait, but significantly constrained sagittal forefoot motion and forefoot sagittal range of motion (ROM) (p < 0.01), which may be detrimental. The Solid Ankle Foot Orthoses (SAFO) constrained forefoot ROM as compared to barefoot gait (p < 0.01). The 6SF model did not confirm that the SAFO can control excessive plantarflexion for those with severe plantarflexor spasticity. The supramalleolar orthosis (SMO) significantly (p < 0.01) constrained forefoot ROM as compared to barefoot gait at the beginning and end of the stance phase, which could be detrimental. The SMO had no effects observed in the coronal plane. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:531–536, 2014.